The Imperial Eunuch: Traces of Hellenistic Institution in Roman Epigraphy (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2017)
Using epigraphic sources the present study focuses on the integration of eunuchs into the social elite of the Roman Empire. Eunuchs in high positions were a new late Ro- man phenomenon. Despite the legislative measures taken against castration of a human being, starting from the fourth century eunuchs filled high offices created especially for them. An analysis of twenty-two inscriptions from the first to the sixth century A.D. reveals the Greek East as a source of the imperial Roman use of eunuchs. The phe- nomenon entered Roman society after being adopted from Asia Minor, and was later institutionalized as an adaptation of local customs of the north-eastern regions of the Roman word. Greek and Latin inscriptions together with historiographic and legisla- tive sources suggest that local social customs, religious positions and positions in the administration held by eunuchs were adopted by the Roman authorities who needed new types of government and social elite. The severe prohibition of castration did not manage to stop this acculturation process, but changed nevertheless its course.